Unethical Practices in Teaching: Causes and Consequences in Nigerian Secondary Schools - Akinyemi, O. C.; Etejere, P. A. O.; Amali, O. O. (International Journal of Educational Management, 2022)
Teaching is one of the oldest professions which has contributed a lot to the development of Nigeria and the survival of humanity, but over time, its standard of practice has depreciated leaving the country that depends on its products in a state of dilemma. This paper discussed unethical practices in teaching; its causes and consequences in Nigerian secondary schools. It explores the concept and characteristics of a profession and spells out the reasons why teaching is a profession. A series of unethical practices in teaching, it causes, consequences in Nigerian secondary schools. The paper concludes by recommending that the standard of the teaching profession can be improved upon by emphasizing the teaching of professional ethics as a compulsory course, as well as examining and supervising secondary school teachers.These would result in the management of differences in human activities which have made schools to contribute meaningfully to human development both in qualitative and quantitative terms